NanoBRET to probe ligand-receptor and receptor-receptor interactions in living cells - Carvalheira Alcobia, Diana (2019)
Increasing evidence has revealed the role of G protein-coupled receptors (GPCRs) in the regulation of signalling responses via complex cross-talk mechanisms with the receptor tyrosine kinase (RTK) family of transmembrane receptors. Vascular endothelial growth factor-a (VEGFa) mediates cancer angiogenesis via binding to its cognate VEGF receptor 2 (VEGFR2). The two class A GPCRs, adenosine A2A receptors and β2-adrenoceptors, have also been intimately involved in cancer angiogenesis, and their activation can contribute to cancer progression and invasion. However, the molecular mechanisms involved in the cross-talk between these receptor families are not well understood.